(untitled) (Journal of the College of Basic Education, 2026)
This research addresses the structural aspects of Anwar Al-Ghassani’s poetry, aiming to uncover the internal structure of his poetic texts and understand the artistic formation mechanisms he employs. The study focuses on elements of language, imagery, meter, rhythm, and semantic construction to illustrate how these elements generate meanings and establish a distinctive poetic discourse. Additionally, the research seeks to read the texts as an integrated system where formal and semantic components interact to produce aesthetic and cognitive effects